Performance analysis in soccer - Link, D. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
This chapter describes how ball actions in soccer can be derived based on continuous-time position data. The underlying heuristic method first determines the individual ball possession by geometric considerations. Each ball possession phase is then assigned a start action as well as an end action. The classification of these actions (e.g. as pass, goal kick or release) is mainly based on the position, direction and speed of the ball as well as the behaviour of the players. The method is an important basis for the further use of position data in game analysis, as it provides, among other things, precise time stamps for actions. In addition, it can help to reduce the considerable manual effort involved in data collection to date and to identify recording errors. In the future, such automations will help ensure that data that has so far only been available in the professional sector can also be made available in the amateur and youth sectors.